2005
DOI: 10.1242/jeb.01769
|View full text |Cite
|
Sign up to set email alerts
|

The kinematics of feeding and drinking in palaeognathous birds in relation to cranial morphology

Abstract: Cranial kinesis is an important feature in avian feeding behaviour and involves the transmission of quadrate movement to the upper bill by the Pterygoid-Palatinum Complex (PPC). The PPC in Palaeognathae is remarkably different from that found in Neognathae. In this study we analyse whether the special morphology of the PPC is an adaptation to the feeding behaviour of the Palaeognathae. Behavioural analyses of the rhea Rhea americana showed that the feeding behaviour of the rhea is typical 'Catch and Throw' beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
101
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(118 citation statements)
references
References 41 publications
15
101
1
1
Order By: Relevance
“…Although the laryngeal mound of ratite species is reported to be smooth (McLelland 1989) and is a feature noted in D. novaehollandiae (Crole and Soley 2010a), many bird species display pharyngeal papillae on the laryngeal mound caudal to the glottis (King and McLelland 1984;Bailey et al 1997;McLelland 1989). The considerable variation in the appearance and number of pharyngeal papillae noted in the present study was a feature not previously reported for R. americana (Faraggiana 1933;Bonga Tomlinson 2000;Gussekloo and Bout 2005). This variability in size, number and appearance suggests that the pharyngeal papillae may be rudimentary in nature and are not an integral part of the functioning of the laryngeal mound.…”
Section: Morpho-functional Considerationssupporting
confidence: 60%
See 3 more Smart Citations
“…Although the laryngeal mound of ratite species is reported to be smooth (McLelland 1989) and is a feature noted in D. novaehollandiae (Crole and Soley 2010a), many bird species display pharyngeal papillae on the laryngeal mound caudal to the glottis (King and McLelland 1984;Bailey et al 1997;McLelland 1989). The considerable variation in the appearance and number of pharyngeal papillae noted in the present study was a feature not previously reported for R. americana (Faraggiana 1933;Bonga Tomlinson 2000;Gussekloo and Bout 2005). This variability in size, number and appearance suggests that the pharyngeal papillae may be rudimentary in nature and are not an integral part of the functioning of the laryngeal mound.…”
Section: Morpho-functional Considerationssupporting
confidence: 60%
“…A renewed interest has recently been shown in the morphology of the upper digestive tract of commercially important ratite species, particularly Struthio camelus (Linnaeus, 1758) (Tivane et al 2006;Porchescu 2007;Jackowiak and Ludwig 2008;Tadjalli et al 2008, Tivane 2008Guimarães et al 2009) and Dromaius novaehollandiae (Latham, 1790) (Crole and Soley 2009a, b, 2010a, b, 2011, as well as in the feeding mechanism employed by this group of birds (Bonga Tomlinson 2000;Gussekloo and Bout 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is more probable that the pores represent the openings of underlying glands, as no histological evidence of taste buds was supplied. Ratite species swallow their food whole, employing the 'catch and throw' (Gussekloo and Bout 2005) or cranioinertial feeding method (Bonga Tomlinson 2000), in which the food lands near or within the oesophageal entrance prior to swallowing. As a result of this method of food intake, there would be a limited need or opportunity for taste during the intra-oral transport of food.…”
Section: Introductionmentioning
confidence: 99%